Digitalizing Self‐Assembled Chiral Superstructures for Optical Vortex Processing. Issue 10 (15th January 2018) - Chen, Peng; Ma, Ling‐Ling; Duan, Wei; Chen, Ji; Ge, Shi‐Jun; Zhu, Zhi‐Han; Tang, Ming‐Jie; Xu, Ran; Gao, Wei; Li, Tao; Hu, Wei; Lu, Yan‐Qing
Abstract: Cholesteric liquid crystal (CLC) chiral superstructures exhibit unique features; that is, polychromatic and spin‐determined phase modulation. Here, a concept for digitalized chiral superstructures is proposed, which further enables the arbitrary manipulation of reflective geometric phase and may significantly upgrade existing optical apparatus. By encoding a specifically designed binary pattern, an innovative CLC optical vortex (OV) processor is demonstrated. Up to 25 different OVs are extracted with equal efficiency over a wavelength range of 116 nm. The multiplexed OVs can be detected simultaneously without mode crosstalk or distortion, permitting a polychromatic, large‐capacity, and in situ method for parallel OV processing. Such complex but easily fabricated self‐assembled chiral superstructures exhibit versatile functionalities, and provide a satisfactory platform for OV manipulation and other cutting‐edge territories. This work is a vital step towards extending the fundamental understanding and fantastic applications of ordered soft matter. Abstract : Digitalized chiral superstructures enable the generation, detection, and demultiplexing of optical vortices in a polychromatic, large‐capacity, and in situ way. Such complex but easily fabricated self‐assembled cholesteric liquid‐crystal superstructures provide a versatile platform for various cutting‐edge territories. This work brings new insights to both fundamental understanding and innovative applications of ordered soft matter.